Gut microbiota, behavior, and nutrition after type 1 diabetes diagnosis: A longitudinal study for supporting data in the metabolic control - Traversi, Deborah; Scaioli, Giacomo; Rabbone, Ivana; Carletto, Giulia; Ferro, Arianna; Franchitti, Elena; Carrera, Deborah; Savastio, Silvia; Cadario, Francesco; Siliquini, Roberta; Cerutti, Franco; Durazzo, Marilena (Frontiers in Nutrition, 2022)
Type 1 diabetes (T1D) risk involves genetic susceptibility but also epigenetics, environment and behaviors. Appropriate metabolic control, especially quickly after the diagnosis, is crucial for the patient quality of life. This study aimed to produce a quantitative comparison of the behavior, nutrition habits and gut microbiota composition between the onset and the 1-year follow-up in 35 T1D children. At follow-up, with the metabolic control, many parameters improved significantly, respect the onset, such as glycated hemoglobin (-19%) and body mass index (BMI) as also nutritional behaviors such as normal caloric intake (+6%), carbohydrate intake (-12%), extra portion request (-4%) and meals distribution during the day. Moreover, glycated hemoglobin decrement correlated with both total and rapid absorption carbohydrates intake (Spearman’s rho = 0.288 95% CI 0.066-0.510, p=0.013) showing as the nutritional behavior supported the insulin therapy efficiency. The next generation sequencing (NGS) analysis of microbiota revealed abundance differences for Ruminococcus bromii, Prevotella copri (higher at onset, p<0.001) and the genera Succinivibrio and Faecalibacterium (lower at onset, p<0.001), as consequence of nutritional behavior but it was not the only changing driver. The qRT-PCR analysis showed significant variations, in particular for Bacteroidetes and Bifidobacterium spp. (+1.56 Log gene copies/g stool at follow-up, p<0.001). During the year, in 11% of the patients, severe clinical episodes occurred (hypoglycemic or ketoacidosis). The likelihood of a severe hypoglycemic episode was modulated when the Methanobrevibacter smithii amount increased (Odds Ratio 3.7 95% CI 1.2-11.4, p = 0.026). Integrated evaluation, including nutritional behavior and microbiota composition, could be considered predictive of the metabolic control management for children cohort with a recent diagnosis of T1D.